Exploring the interplay of clinical, ethical and societal dynamics: two decades of Medical Assistance in Dying (MAID) on psychiatric grounds in the Netherlands and Belgium - Verhofstadt, Monica; Marijnissen, Radboud; Creemers, Daan; Rasing, Sanne; Schweren, Lizanne; Sterckx, Sigrid; Titeca, Koen; van Veen, Sisco; Pronk, Rosalie (Frontiers in Psychiatry, 2024)
Psychiatric Grounds (MAID-PG), focusing on ethical, clinical, and societal perspectives. Two themes are explored. First, the growing number of young MAID-PG requestors and the public platform given to MAID-PG requests. Ethically, media portrayal, particularly of young patients' testimonials, requires scrutiny for oversimplification, acknowledging the potential for a Werther effect alongside the absence of a Papageno effect. This highlights the need for better communication policies for media purposes. Second, cautionary considerations regarding psychiatric care adequacy are addressed. In MAID-PG this includes reasons underlying psychiatrist reluctance to engage in MAID-PG trajectories, leading to growing waiting lists at end-of-life-care centers. Addressing current shortages in psychiatric care adequacy is crucial, necessitating less narrow focus on short-term care trajectories and recovery beside transdiagnostic treatment approaches, expanded palliative care strategies, and integrated MAID-PG care.